The development of a smart health awareness message framework based on the use of social media: quantitative study - Alsisi, Elaf Ali; Al-Ashaab, Ahmed; Abualfaraa, Wadhah Ahmed (JMIR Publications, 2020)
Background: Social media has recently provided a remarkable means of delivering health information broadly and in a cost-effective way. Despite its benefits, some difficulties are encountered in attempting to influence the public to change their behavior in response to social media health messages. Objective: This study aimed to explore the factors that affect individuals’ acceptance of using social media as a tool for receiving health awareness messages and adapting such content accordingly by developing a smart health awareness message framework. Methods: A quantitative method was adapted to validate the hypotheses and proposed framework through the development of a survey based on the technology acceptance model with the extension of other constructs. The survey was distributed on the web to 701 participants from different countries via Qualtrics software; it generated 391 completed questionnaires, and the response rate was 55.8% (391/701). Results: Of the 391 respondents, 121 (30.9%) used social media platforms often during the week, and 27 participants (6.9%) did not use social media. In addition, 24.0% (94/391) of the respondents used these platforms to seek health information. On the basis of the results, perceived usefulness (β=.37; P<.001), gain-framed message (β=.04; P<.001), and loss-framed message (β=.08; P<.001) were seen to positively and significantly influence people’s intention to use social media as a means to spread information about health promotion. The proposed smart health awareness message framework identifies 64.2% of the variance in intention to use, 55.4% of the variance of perceived usefulness, and 26.2% of the variance of perceived ease of use. Conclusions: This study sheds light on the factors that are associated with people’s intention to use and adopt social media in the health promotion domain. The findings reveal that the intention of using social media for health awareness purposes is positively impacted by the perception of usefulness of social media and the design of health messages. Future research might seek to explore other factors that relate to people’s behavior. This point of view will assist health organizations in developing their health messages more effectively and to be patient friendly.
Keywords: technology acceptance theory; eHealth; health promotion; health awareness; health promotion and social media